1998
DOI: 10.1128/aac.42.6.1454
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure-Activity Relationship Studies of a Series of Sulfa Drugs as Inhibitors of Pneumocystis carinii Dihydropteroate Synthetase

Abstract: Sulfone and sulfanilamide sulfa drugs have been shown to inhibit dihydropteroate synthetase (DHPS) isolated from Pneumocystis carinii. In order to develop a pharmacophoric model for this inhibition, quantitative structure-activity relationships (QSAR) for sulfa drugs active against DHPS have been studied. Accurate 50% inhibitory concentrations were collected for 44 analogs, and other parameters, such as partition coefficients and molar refractivity, were calculated. Conventional multiple regression analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…From the given structure of drug molecules (see insets in Figures and S1), one could intuitively expect a high lipophilicity because of the presence of aromatic ring with delocalized π-electrons. These drugs, however, have isolated negative charges on the carboxylate or amide group once deprotonated, which are unshielded in their molecular structures as well. Such localized negative charges could dominate the effective hydrophilicity of the drug ions, especially when they transfer across a water/DCE interface. In fact, nanopipet voltammetry in this study revealed an extremely high value of effective hydrophilicity for deprotonated quinolone and sulfonamide ions.…”
Section: Resultsmentioning
confidence: 99%
“…From the given structure of drug molecules (see insets in Figures and S1), one could intuitively expect a high lipophilicity because of the presence of aromatic ring with delocalized π-electrons. These drugs, however, have isolated negative charges on the carboxylate or amide group once deprotonated, which are unshielded in their molecular structures as well. Such localized negative charges could dominate the effective hydrophilicity of the drug ions, especially when they transfer across a water/DCE interface. In fact, nanopipet voltammetry in this study revealed an extremely high value of effective hydrophilicity for deprotonated quinolone and sulfonamide ions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of various anti- Pneumocystis agents including trimethoprim-sulfamethoxazole, pentamidine, clindamycin-primaquine, and atovaquone, recent concerns support the need to develop additional agents [7577]. While these agents are effective in reducing pathogen burden, drug-related toxicities limit use in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than computing ligand−receptor binding energies (a nontrivial task for metal-binding enzymes such as MMPs), these methods sample steric and electrostatic fields (CoMFA) or calculate similarity indices (CoMSIA) surrounding an established compound set and then correlate differences in those fields or indices with experimental biological activity. Both CoMFA and CoMSIA have been shown in multiple studies to be powerful and effective techniques for designing novel ligands, improving the potency of existing inhibitors, mapping previously unmodeled active-site properties, and clarifying mechanisms of action.…”
Section: Methodsmentioning
confidence: 99%